Contrato realidad estatal: implicaciones frente a la sentencia de unificacion SUJ-025-CE-S2-2021 del Consejo de Estado (2023)
The Colombian legal system allows public entities to carry out contractual ties through the provision of services or support to the management of human talent in order to carry out activities necessary for the operation of the state apparatus. The administration today has generated in an exorbitant way the improper use of this contracting modality, compared to the employees per plant, for which a form of fraud by the State of the guarantees, benefits and labor claims of the contractor would be configured. Which have been positivized in the national legal system and international instruments as an essential part of the fundamental right to decent work in the face of the guarantees that are inherent in the employment relationship. Due to the above, this study was carried out as a legal investigation, through the analytical method, which was treated from the use of documentary instruments, which were categorized from different formal sources of the Colombian legal system, such as: laws, decrees, jurisprudence, doctrine, treaties, pacts, agreements, the categories of formal analysis were validated by sources of legal interpretation, which according to the criteria of methodological rationalization allow to identify the epistemological guidelines that were taken as axes of reference: legal journals, concepts, resolutions, theses.